Inadvertent intravenous injection of carboprost in a COVID-19-positive patient: A case report - Nazia Nazir; Deepti Chopra (Wolters Kluwer Medknow Publications, 2022)
We present a case report of an inadvertent administration of intravenous carboprost in a COVID-19-positive parturient who was taken up for an emergency caesarean section for meconi um-stained liquor. Unintentionally, the patient was administered intravenous carboprost instead of ondansetron. The patient developed breathlessness, uneasiness and hypertension. Despite the mishap, the patient fully recovered and was discharged after 15 days. Although the medical error in the present case was non-harmful, the treating doctor discussed the case with the patient. Conclusion: A case with inadvertent intravenous administration of carboprost in a COVID-19-positive parturient is reported with a good outcome.